Boosting Students’ Reading Achievement Through Kahoot! And Choral Reading Strategy - Lastari, Siti; Ifadah, Muhimatul; Wijayatiningsih, Testiana Deni (Jurnal Bahasa Inggris, 2022)
Reading is an activity to improve students' knowledge. However, some problems happened to Class X Social 4 SMA N 9 Semarang students. They had low activities in reading English text, so their vocabulary attainment needed to be improved. Based on the issues, this research discusses the effect of Kahoot! application and choral reading strategy to improve students' motivation in reading. It aims to know how choral reading strategy and Kahoot! can improve students' motivation in reading narratives and what factors significantly affect students' reading motivation. This research used classroom action research to collect the data and a quantitative approach to analyze the data. The subject of this research is the students' Class X Social 4 SMA N 9 Semarang. The result of this research got 47.83% of students with low motivation in English subject, and in the pre-test, students' mean score was 77.2. It was better after using the choral reading strategy and Kahoot! application. It could be seen from the students' mean score in post-test one that was 80, and post-test two was 87.82. All in all, students' reading motivation improved after using the choral reading strategy and Kahoot! Application in the teaching-learning process. Choral reading strategy and Kahoot! application is recommended to teach English material, especially in reading.